Identificação de parâmetros em sistemas rotativos utilizando funções de otimização e observadores de estado - Oliveira, Lucas Rangel de [UNESP] (2015)
A rotating machine is composed of many interconnected components working together. This mutual influence can cause a wide range of phenomena during operation. Unbalancing, misalignment and failure in ball bearings are mainly responsible for the vibration of such equipment. One solution to avoid such problems is the constant monitoring of machines in order to predict a more severe damage. In this environment, there is concern in the development of new techniques for detection and troubleshooting. One of the techniques is now widespread the identification of stiffness and damping of the bearing and the excitation forces of the system. For the development of these methods is the need to build mathematical models that represent the mechanical behavior and is useful in predicting system response. In this context, this project proposes the estimation of stiffness and damping of the bearings - from experimental data - and the identification of unbalance forces using three different methods: Fourier series, Legendre polynomials and Chebyshev